Literasi Pengelolaan Keuangan Usaha untuk Pelaku UMKM Binjai Estate - Maryam Monika Rangkuti; Efry Kurnia (Lembaga Pengembangan Kinerja Dosen, 2025)
The limited knowledge of MSME entrepreneurs in Binjai Estate in managing their business finances affects the business continuity of MSMEs, causes errors in determining the amount of the cost of goods sold resulting in errors in determining the amount of the selling price, resulting in difficulty of increasing competitiveness which will affect the level of sales and profits of MSMEs. The purpose of these activities is to help MSME players increase their sales by providing simple financial management training and promoting their merchandise through social media and online shops so that later they can increase MSME sales. The methods used are observation, interview, and documentation methods. The results of this service activity are that Bandrek Jahe Merah and Gedebog Pisang MSMEs can already recognize the importance of business financial management and identify company assets to be separated from personal assets. However, further training is needed to assist businesses in making budgets and determining the cost of production and the cost of goods sold to determine the selling price of their products.